2008
DOI: 10.1016/j.expneurol.2008.08.009
|View full text |Cite
|
Sign up to set email alerts
|

LAU-0901, a novel platelet-activating factor antagonist, is highly neuroprotective in cerebral ischemia

Abstract: Middle cerebral artery occlusion Behavioral Histopathology Local cerebral blood flow Platelet-activating factor (PAF) is a bioactive phospholipid that accumulates during ischemia-reperfusion and is involved in the activation of platelets, neutrophils, and pro-inflammatory signaling. PAF has been suggested to enhance brain ischemia-reperfusion damage. LAU-0901, a novel PAF receptor antagonist, was examined in models of focal cerebral ischemia in rats and mice. Sprague-Dawley rats were anesthetized and received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…LAU-0901 was also evaluated in animal models of focal cerebral ischemia in rats and mice and showed marked infarct volume reduction and neurobehavioral improvement at seven days of survival (Belayev et al 2008). LAU-0901 treatment (30, 60 and 90 mg/kg) significantly reduced total corrected infarct volume compared to vehicle rats by 76, 88 and 90%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LAU-0901 was also evaluated in animal models of focal cerebral ischemia in rats and mice and showed marked infarct volume reduction and neurobehavioral improvement at seven days of survival (Belayev et al 2008). LAU-0901 treatment (30, 60 and 90 mg/kg) significantly reduced total corrected infarct volume compared to vehicle rats by 76, 88 and 90%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have shown that LAU-0901 improved behavior and reduced brain infarction in focal cerebral ischemia in rats and mice (Belayev et al 2008). The dose-response studies in rat and mouse models of transient middle cerebral artery occlusion (MCAo) showed that 60 mg/kg dosage was highly neuroprotective; thus, this dose was applied in this study (Belayev et al 2008). The objective of the present study was to test the hypothesis that acute LAU-0901-induced neuroprotection endures in animals allowed to survive for several weeks after focal ischemic insult.…”
Section: Introductionmentioning
confidence: 99%
“…At present time instinctively occurring PAF antagonist exists as a specific grade of therapeutic agents against different diseases either of immunological or non-immunological types [6]. Most important, activation of PAF could further aggravate cerebral neuronal damage induced by ischemic reperfusion [7]. Hence, PAF antagonist is frequently used to lessen cerebral neuron injury [8].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, PAF has been reported to play an important role in many pathophysiological processes including cerebral edema and cerebral ischemia-reperfusion injury through interactions with PAFR1718. PAFR, which belongs to G protein coupled receptors superfamily, is a seven transmembrane proteins that expressed extensively throughout the brain including microglia and neurons and has been reported to be activated by interating with PAF1920.…”
mentioning
confidence: 99%